PERBEDAAN KECERDASAN EMOSI ANTARA SISWA SMA SWASTA NASIONAL NAMOTERASI (SEKOLAH REGULER) DAN SMA AGAMA DI SMAS GKPI PADANG BULAN (SEKOLAH AGAMA) - Rhiesqi Chintia Fonna; Emarco Sani Tribrata Simaremare (Jurnal Genta Mulia, 2025)
This study aims to examine the differences in emotional intelligence between students from regular senior high schools and religious-based senior high schools. The research involved 265 students from grade X and XI, drawn from SMAS Nasional Namoterasi (regular school) and SMAS GKPI Padang Bulan (religious school). An ex post facto method with a comparative approach was applied, using a questionnaire that assessed five key aspects of emotional intelligence: self-awareness, emotional regulation, self-motivation, empathy, and relationship management. The instrument was found to be both valid and reliable (α = 0.954). Normality and homogeneity tests confirmed that the data were normally distributed and homogeneous. A t-test analysis revealed a significant difference between the two groups (p < 0.05), showing that students in the religious school exhibited significantly higher emotional intelligence levels compared to those in the regular school. The empirical mean of emotional intelligence in the religious school exceeded the hypothetical mean, while the regular school fell below it. These findings suggest that the integration of spiritual values and religious activities in the curriculum significantly contributes to students' emotional development. This study highlights the importance of incorporating moral and emotional values into education to support the holistic development of students.